PENGARUH TRANSAKSI PIHAK BERELASI DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK TAHUN 2017 SAMPAI DENGAN 2019 (Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia ): THE INFLUENCE OF RELATED PARTY TRANSACTIONS AND PROFITABILITY ON TAX AGGRESSIVINESS FOR THE YEAR (In Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange) - Aprianingsih; Manurung , Jean P; Lumbantoruan , Rutman (Fundamental Management Journal, 2021)
Related party transactions are transactions between parties that have a special relationship or are the source of problems arising from transfer pricing practices. This study aims to determine the effect of related party transactions and profitability on aggressiveness in 2017 to 2019 in Food and Beverage Sub-Sector Manufacturing Companies listed on the Indonesia Stock Exchange. The sampling technique is purposive sampling of 14 companies with sample criteria, namely food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2019. The results of the study show a positive relationship to tax aggressiveness, which indicates that there is no effect between related party transactions and aggressiveness. tax. The related party transaction variables and profitability show that there is no effect on tax aggressiveness in food and beverage sub-sector manufacturing companies on the IDX in 2017 to 2019. Suggestions for companies with high profits should maximize their tax planning properly without having to do tax aggressiveness. Keywords: Related Party Transactions, Profitability, Tax Aggressivness